1981
DOI: 10.1182/blood.v58.6.1100.1100
|View full text |Cite
|
Sign up to set email alerts
|

Mouse megakaryocytes secrete acetylcholinesterase

Abstract: Acetylcholinesterase (AchE), an essentially specific and early marker of rodent thrombocytic series, in several tissues acts both as a constituent of the cellular membrane and as a secretory enzyme. This study presents the ultrastructural transport and fate of this substance in the megakaryocytes of mouse bone marrow, using Tranum-Jensen and Behnke's adaptation of the indirect thiocholine method. It is shown that megakaryoblasts and megakaryocytes undergo a typical secretory cycle consisting of (1) enzyme synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…In studies reported elsewhere (221, we have sorted these different megakaryocyte subpopulations for analysis of their metabolic capacity to synthesize thromboxane B2, which we have suggested previously (21) may serve as a potential metabolic marker of differentiation. In future studies we plan to investigate the complexities raised by the results of the present study; to do so, we will use monoclonal antibodies directed to megakaryocyte subpopulations and platelets as well as make fluorescent measurements of acetylcholinesterase activity (10,15), parameters that may prove useful as additional probes of megakaryocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In studies reported elsewhere (221, we have sorted these different megakaryocyte subpopulations for analysis of their metabolic capacity to synthesize thromboxane B2, which we have suggested previously (21) may serve as a potential metabolic marker of differentiation. In future studies we plan to investigate the complexities raised by the results of the present study; to do so, we will use monoclonal antibodies directed to megakaryocyte subpopulations and platelets as well as make fluorescent measurements of acetylcholinesterase activity (10,15), parameters that may prove useful as additional probes of megakaryocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To inhibit cholinesterase activity, 0.2 mM DFP (final concentration) a serine protease inhibitor, or 0.2 mM (final concentration) 1,5-bis (4-allyldimethylammoniumphenyl)-pentan-3-one dibromide, a specific AchE inhibitor (BW248C51; Sigma; Paulus et al, 1981) was diluted in the Tris-Triton-DTNB solution and added to each well.…”
Section: Inhibitor Studiesmentioning
confidence: 99%
“…Since previous workers have reported that a small quantity of AchE is present in murine red cells (Paulus et al, 1981), platelet-free red cells were prepared as described and assayed for AchE activity. No significant activity was noted using concentrations of red cells whose intrinsic OD due to hemoglobin was higher than is ever observed in marrow cultures (data not shown).…”
Section: Cellular Specificity Of Achementioning
confidence: 99%
“…This finding has led to the hypothesis that autoregulation of megakaryocytes in rodents is controlled by acetylcholinesterase. Data presented by Puulus et al [26] support this hypothesis, i.e., the secretion of acetylcholinesterase by megakaryocytes was thought to control the proliferation of megakaryocyte progenitors. The injection of Neostigmine (an inhibitor of acetylcholinesterase) into mice elevated the percentage of small acetylcholinesterase-positive (SAChE+) cells [25].…”
Section: Autoregulation Of Megakaryocytopoiesismentioning
confidence: 81%
“…Megakaryocytopoiesis is clearly regulated, to a large degree, by the number and/or function of circulating platelets. However, evidence also exists for autoregulation of megakaryocytopoiesis [l, [22][23][24][25][26]. It has been observed that increased numbers of mature megakaryocytes in the marrow of rodents will decrease the number of megakaryocytic progenitors, and megakaryoqtic macrocytosis occurs in several conditions associated with low numbers of megakaryocytes [23].…”
Section: Autoregulation Of Megakaryocytopoiesismentioning
confidence: 99%